GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 327 species occurrences available in GBIF matching the query: TaxonKey: Felis concolor Linnaeus, 1771. The dataset includes 327 records from 27 constituent datasets: 3 records from Western Australian Museum provider for OZCAM. 2 records from Mammal specimen database of Kanagawa Prefectural Museum of Natural History. 1 records from (UTC) University of Tennessee Mammals Collection. 3 records from Mammal collection of National Museum of Nature and Science. 17 records from UNSM Vertebrate Specimens. 2 records from naturgucker. 5 records from Mammals collection (ZM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 4 records from Database Schema for UC Davis Wildlife museum. 7 records from Paleobiology Database. 9 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 30 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 1 records from UCM Mammal Collection (Arctos). 2 records from CUMV Mammal Collection (Arctos). 4 records from New Mexico Biodiversity Collections Consortium database. 2 records from Mammal collection, Natural History Museum, University of Oslo. 13 records from Mammals housed at MHNG, Geneva. 4 records from University of Ghent - Zoology Museum - Vertebratacollectie. 1 records from Lund Museum of Zoology (MZLU). 7 records from South Australian Museum Australia provider for OZCAM. 8 records from UMZC Zoological Specimens. 28 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mammalia. 10 records from Museum of Comparative Zoology, Harvard University. 99 records from University of California Museum of Paleontology. 1 records from NMNH occurrence DwC-A. 24 records from Mamíferos de la colección del Instituto Alexander von Humboldt. 19 records from Natural History Museum (London) Collection Specimens. 21 records from AMNH Mammal Collections.
Keywords: GBIF; biodiversity; species occurrences